The "fintech revolution" is here! The disruptive impact of fintech on retail financial practices - Gordon Kuo Siong Tan (Finance and Society, 2022)
Fintech is celebrated for its disruptive and democratizing qualities that dis/reintermediates the finance value chain. Claims of a 'fintech revolution' assume that fintech is 'disruptive' because of its innovative capabilities, but the extent to which these disruptive forces have reconfigured consumer financial knowledge and practices is not well understood. Using a questionnaire to survey retail consumers in Singapore on their use of fintech in performing different financial tasks, this article critically examines these claims of disruption and democratization by grounding them in the financial behaviors of consumers as informed by a financial ecologies approach. The results show a limited impact of fintech in shaping consumer financial behaviors. Respondents use fintech mainly for basic transactional purposes like making mobile payments and account management, but not so much for more complex matters like savings, investing and credit. The findings also reveal a 'stickiness' in financial behaviors that emphasizes the high touch points of human interaction. This study illustrates fintech's variegated material outcomes by highlighting the unevenness in consumption of digital financial services and the enduring importance of human relationality in financial decision making.
Keywords: 300; Fintech; financial ecologies; democratization; financial behaviors; roboadvisors; Singapore